Occurrence of Thromboembolism in Paediatric Patients With Inflammatory Bowel Disease: Data From the CEDATA-GPGE Registry - De Laffolie, Jan; Ballauff, Antje; Wirth, Stefan; Blueml, Carolin; Rommel, Frank Risto; Claßen, Martin; Laaß, Martin; Lang, Thomas; Hauer, Almuthe Christina; , the CEDATA-GPGE Study Group (Frontiers in Pediatrics, 2022)
Objective: In patients with inflammatory bowel disease (IBD), the risk of thromboembolism (TE) is increased, representing a relevant cause of morbidity and mortality. In contrast to other extraintestinal IBD manifestations, TE receives much less attention because of its low incidence, estimated merely 0.4-0.9% in hospitalised children with IBD. Methods: Cases with TE, as documented in the German-Austrian Pediatric IBD registry CEDATA-GPGE, were analysed retrospectively. For all patients with signs of TE, a questionnaire was filled in by the treating paediatric gastroenterologist. Results: Over 10 years, 4,153 paediatric IBD patients (0-18 years) were registered in the registry and 12 of them identified with TE. Eight patients were diagnosed with ulcerative colitis (UC), three with Crohn’s disease (CD), and one with IBD-unclassified. Median age at IBD diagnosis was ten years and at manifestation of TE 13 years, resp., with a median latency to TE of two years. Prevalence of TE was 0.3%, with a significantly higher risk for UC than CD patients (OR 5.9, CI 1.56-22.33, p=0.008). More girls than boys were affected (f:m = 7:5) without reaching significance. 90% of patients experienced TE during active disease, with relevant cerebral and limb involvement in 6/12 patients. Various risk factors, e.g., hospitalisation, coagulopathy or anaemia were identified. TE management included intensive care and surgery. 11/12 patients recovered fully; one patient has focal epilepsy as a sequela. Conclusion: Paediatric IBD patients have a substantially increased risk for TE. Risk factors as those identified should be considered when managing paediatric IBD and preventive measures for those hospitalised taken routinely. Initiating pharmacological thromboprophylaxis is challenging for lack of published trials on efficacy and safety in paediatric IBD, but should be considered carefully in each case.